Risky air: an analysis of risk perceptions, punitive attitudes, and regulatory support towards corporate violations of the Clean Air Act - Tullis, Matthew Thomas, author; Shelley, Tara O'Connor, advisor; Hogan, Michael, committee member; Davis, Charles, committee member (Colorado State University. Libraries, 2014)
This research explores whether perceptions of environmental risk influences support for social control measures, with specific reference to violations of the Clean Air Act. Drawing on national survey data collected between April and September of 2013, the research assesses whether environmental risk perception affects support for social control measures in the form of regulation and punishment. Risk perception is measured using a risk theory developed by Robert O'Connor, Richard J. Bord, and Ann Fisher (1999), which includes three components: 1) problem awareness, 2) negative consequences to be experienced by oneself and others, and 3) knowledge of the causes of the problem. The research findings indicate that perceived negative consequences to self and/or others and knowledge of the causes of the problem are significant predictors of regulatory support while problem awareness was not. Two of the three forms of risk were generally not relevant for understanding public support of punishment in response to corporate environmental crime. The notable exception was negative consequences to self and others, where people who favored stricter forms of punishment were those who perceived the most negative consequences associated with air pollution. In sum, it appears that O'Connor et al. (1999) risk perception theory is salient for understanding regulation but only partially relevant for understanding punishment preferences for environmental corporate crime.
Keywords: Clean Air Act; risk; green criminology; environmental attitudes; corporate violations